Study of Effectiveness of Sodium Hydroxide (NaOH) and Sodium Carnonate (Na2CO3) on the Impurities Removal of Saturated Salt Solution - Caecilia Pujiastuti; Yustina Ngatilah; Ketut Sumada; Sri Muljani (Nusantara Science and Technology Proceedings)
Increasing the quality of salt can be done through various methods such as washing of salt by saturated salt solution, re-crystallization or twice crystallization, ion exchange methods and others. In the process of salt quality improvement by re-crystallization method where salt product diluted with water to form saturated solution and re-crystallized through heating process. The re-crystallization method can be done by chemicals or without chemical added. In this research is proposed a concept that before the saturated salt solution is re-crystallized needed chemicals added for removal of the impurities such as magnesium ion (Mg), calcium (Ca), potassium (K) and sulfate (SO4) is contained in a saturated salt solution. The chemical reagents that used are sodium hydroxide (NaOH) 2 N and sodium carbonate (Na2CO3) 2 N. This research aims to study effectiveness of sodium hydroxide and sodium carbonate on the impurities removal of magnesium (Mg), calcium (Ca), potassium (K) and sulfate (SO4). Based on research results found that the addition of sodium hydroxide solution can be decreased the impurity ions of magnesium (Mg) 95.2%, calcium ion (Ca) 45%, while the addition of sodium carbonate solution can decreased magnesium ion (Mg) 66.67% and calcium ion (Ca) 77.5%, but both types of materials are not degradable sulfate ions (SO4). The sodium hydroxide solution more effective to decrease magnesium ion than sodium carbonate solution, and the sodium carbonate solution more effective to decrease calcium ion than sodium hydroxide solution.